If it's not what You are looking for type in the equation solver your own equation and let us solve it.
23m+46=16m+32
We simplify the equation to the form, which is simple to understand
23m+46=16m+32
We move all terms containing m to the left and all other terms to the right.
+23m-16m=+32-46
We simplify left and right side of the equation.
+7m=-14
We divide both sides of the equation by 7 to get m.
m=-2
| 16x^2+64x+60= | | (-14+2i)-(24+26i)= | | 3(x+1)-ax=x+4 | | s^2+7s=1 | | 3(-4)-8y=24 | | 23m+22=46-22m | | 3x^3-48xy^2=0 | | 23m+32=46-22m | | 5y^2-15=x | | -1+21(4.5)= | | 2a-8=-10 | | 23m+3=46-22m | | 23m+3=46-26 | | -8(3p-2q)= | | 23m+3=46-22 | | 64x^3+729= | | w/3-6=--8 | | 3(x+2)=(2x-1)-12 | | s^2+7s=5 | | 6x-2-2x-8+5x+1=18 | | -1+21x+23=27x-5 | | (-n)-9=3 | | 4x-10=21 | | -9+9a=36 | | s(-4-8t)= | | 3(x+2)-(5x+1)=-2x-5(-x-2) | | -3n(2n+1)+7=-5 | | -4d-8=50-6 | | 30/5=14/c | | -1/4m=5 | | -10b-25-3b=4b-1 | | 60+12c= |